Impacts of temperature, morpholine, and chronic radiation on the embryonic development of round whitefish (Prosopium cylindraceum). (30th July 2018) - Lim, Michael Y.‐T.; Manzon, Richard G.; Somers, Christopher M.; Boreham, Douglas R.; Wilson, Joanna Y.
Abstract: During incubation, round whitefish embryos may experience fluctuating or elevated temperatures from natural (e.g., seasonal temperature changes) and/or anthropogenic sources. Anthropogenic sources like once‐through cooling discharges from nuclear power plants can also expose embryos to chemicals (e.g., morpholine) and/or radiation. To examine the effects of these potential stressors on embryogenesis, round whitefish were incubated under fluctuating or constant temperatures, with morpholine or 137 Cs gamma rays. We report the percentage of prehatch and posthatch mortality, developmental rate, hatch dynamics, and morphometrics at 4 development stages. Embryos reared at constant temperatures had delayed developmental stage onset and median hatch, higher mortality at constant 8 °C, and lower mortality at ≤5 °C, compared with embryos reared under seasonal temperature regimes. Embryos incubated with ≥500 mg L −1 morpholine (>200× regulatory limits) had advanced hatch, reduced body size, and increased prehatch (100% at 1000 mg L −1 ) and posthatch (≈95% at 500 mg L −1 ) mortality compared with controls. Relative to controls, embryos irradiated with ≥0.16 mGy/d had larger body mass early in development, and all irradiated embryos had decreased posthatch mortality; the lowest dose was >300× discharge limits. Our study suggests that fluctuating or elevated temperatures and high‐dose morpholine can alter development rate, hatch dynamics, and growth, and/or increase mortality compared with embryos reared at constant temperatures of ≤5 °C; conversely, low‐dose irradiation had transient developmental effects but may benefit early posthatch survival. Environ Toxicol Chem 2018;37:2593–2608. © 2018 SETAC.